2022
DOI: 10.3390/su14031906
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Induced Displacement and Relocation Options: A Case Study of Owner Driven Settings in Sri Lanka

Abstract: Disaster induced displacement is one of the most frequent phenomena occurring in the contemporary world and has been aggravated by factors such as climate change. With the systematic interpretation of disaster risks, planned relocation has been recognized as a durable solution for post-disaster reconstruction and disaster mitigation. Planned relocation initiatives that have been executed as post-disaster reconstruction initiatives in Sri Lanka have mainly followed donor driven and owner driven approaches. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Likewise, Tharim et al [13] identified that the post-flood resettled communities in Malaysia were unsatisfied with the housing design, the size of the house, and the indoor air temperature during the daytime. Senanayake et al [4] stressed that community involvement in the planning and alteration of the housing design will increase housing satisfaction. Meanwhile, Pormon et al [24] conducted a study on post-disaster resettlement in the Philippines after Typhoon Haiyan and found that cultural activities played a significant role as common predictor variables in determining residential satisfaction.…”
Section: Factors Influencing Housing Satisfaction In Post-disaster Re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Tharim et al [13] identified that the post-flood resettled communities in Malaysia were unsatisfied with the housing design, the size of the house, and the indoor air temperature during the daytime. Senanayake et al [4] stressed that community involvement in the planning and alteration of the housing design will increase housing satisfaction. Meanwhile, Pormon et al [24] conducted a study on post-disaster resettlement in the Philippines after Typhoon Haiyan and found that cultural activities played a significant role as common predictor variables in determining residential satisfaction.…”
Section: Factors Influencing Housing Satisfaction In Post-disaster Re...mentioning
confidence: 99%
“…Resettlement entails the planned, assisted, and permanent relocation of displaced populations by introducing them to a new built environment [2,3]. It is considered a durable solution for post-disaster reconstruction and mitigation [4]. However, despite significant financial investment and policy provisions, many resettlement projects have produced limited outcomes in resettlement projects, which often overlook the long-term well-being of the affected communities [5].…”
Section: Introductionmentioning
confidence: 99%
“…Disasters are a frequent phenomenon worldwide, and climate change is accelerating the hazard of disasters [1]. The world has a total forest area of 4.06 billion ha, which accounts for 31% of the total land area [2].…”
Section: Introductionmentioning
confidence: 99%
“…Natural disasters are becoming increasingly prevalent worldwide (Senanayake et al, 2022). In particular, large-scale forest soil sediment disasters induced by complex topographical and climatic factors destroy forests and cause loss of life, property destruction, and infrastructure damage (Stanley and Kirschbaum, 2017;Habumugisha et al, 2022).…”
Section: Introductionmentioning
confidence: 99%